The Application Of Literacy In The Community Through The Rimba Bulan Reading Room - Zikri, Atika; Agustina, Agustina (Jurnal Syntax Transformation, 2025)
Community literacy is an essential foundation for building civilization and competitive human resource quality in the digital era. The low reading interest among communities, especially in areas with limited access to library facilities, poses a serious challenge to national literacy development. Rimba Bulan Reading Space emerges as a community-based alternative solution to enhance community literacy culture. This article aims to analyze the implementation of community literacy through Rimba Bulan Reading Space using a descriptive approach. The methods employed include direct observation of literacy activities, interviews with managers and participants, and documentation studies of programs. Research findings indicate that Rimba Bulan Reading Space successfully increased children's and adolescents' reading interest through various programs such as shared reading, mobile reading corners, creative writing training, and book discussions. Supporting factors for success include active volunteer participation, local community support, and collaboration with various parties. Constraints faced include limited operational funding, insufficient new book collections, and program continuity. This research recommends strengthening managerial capacity, diversifying funding sources, and establishing strategic partnerships with government and private sectors for the sustainability of community literacy programs.